2015
DOI: 10.3109/03639045.2015.1118491
|View full text |Cite
|
Sign up to set email alerts
|

Lipid-based nanocarrier for quercetin delivery: system characterization and molecular interactions studies

Abstract: The flavonoid quercetin (QU) is a naturally occurring compound with several biological activities. However, the oral bioavailability of this compound is very low due to the high pre-systemic metabolism in the colon and liver and its low water solubility. In this context, the development of QU-loaded nanocarriers (NEs) is a promising approach to improve the drug oral bioavailability. This study investigates the variation of the concentration of 12-hydroxystearic acid-polyethylene glycol copolymer, lecithin and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Zhang et al [94] aimed to improve the oral absorption of baicalin, which has low solubility and poor permeability, by using a micellar formulation comprised of the carriers Pluronic P123 copolymer and sodium taurocholate. Sustained release profile of baicalin-loaded mixed micelles, in in vitro drug release experiment, held in several pH conditions, showed 14% drug released after 2 h in gastric conditions and 54% release within 48 h in intestinal conditions, compared to 34% and 79% release [105], nanoparticles [106][107][108][109][110], phytosome [111], nanoliposome [112], mixed micelles [113,114], SNEDDS [115,116], nanocarrier [117,118], nanoemulsion [119], nanosuspension [ Mixed micelles [129,130], nanoparticles [131,132], solid dispersion [133,134] , SNEDDS [135] , SMEDDS [136], lipid carrier [137], copolymeric micelles [138], exosomes [139] Naringenin DENV, HCV SNEDDS [140], solid dispersion [141], nanoparticles [142,143] , liposome [144], nanosuspension [145,146] In vitro uptake studies, carried out with a caco-2 cell line, determined the absorption of baicalin within the mixed micelles and verified their internalization ability. Baicalin-loaded ST-P123-MMs formulation achieved high oral bioavailability (Fig.…”
Section: Delivery Of Herbal Extracts and Phytochemicalsmentioning
confidence: 99%
“…Zhang et al [94] aimed to improve the oral absorption of baicalin, which has low solubility and poor permeability, by using a micellar formulation comprised of the carriers Pluronic P123 copolymer and sodium taurocholate. Sustained release profile of baicalin-loaded mixed micelles, in in vitro drug release experiment, held in several pH conditions, showed 14% drug released after 2 h in gastric conditions and 54% release within 48 h in intestinal conditions, compared to 34% and 79% release [105], nanoparticles [106][107][108][109][110], phytosome [111], nanoliposome [112], mixed micelles [113,114], SNEDDS [115,116], nanocarrier [117,118], nanoemulsion [119], nanosuspension [ Mixed micelles [129,130], nanoparticles [131,132], solid dispersion [133,134] , SNEDDS [135] , SMEDDS [136], lipid carrier [137], copolymeric micelles [138], exosomes [139] Naringenin DENV, HCV SNEDDS [140], solid dispersion [141], nanoparticles [142,143] , liposome [144], nanosuspension [145,146] In vitro uptake studies, carried out with a caco-2 cell line, determined the absorption of baicalin within the mixed micelles and verified their internalization ability. Baicalin-loaded ST-P123-MMs formulation achieved high oral bioavailability (Fig.…”
Section: Delivery Of Herbal Extracts and Phytochemicalsmentioning
confidence: 99%
“…The evaluation showed that the data fit better in the Higuchi model (r 2 = 0.9144), demonstrating that the release is controlled by the drug diffusion process through the nanocarrier matrix ( Table 3 ). After confirming the Higuchi model as the most suitable to adjust the data of NLC-QU release, the release mechanism using the Koresmeyer–Peppas model and the data up to 60% of release from the initial concentration were evaluated [ 26 , 27 ]. In this analysis, the correlation coefficient ( r 2 ) obtained was 0.9081, and the diffusion coefficient ( n ) was 0.7, which indicates an anomalous transport (non-Fickian diffusion), in which the release mechanism is governed by the diffusion and rearrangement of the nanocarrier structure, in a swelling or similar behavior.…”
Section: Resultsmentioning
confidence: 99%
“…An analytical HPLC method previously developed and validated according to ICH (2005) was used to determine the content and recovery rate of QU from the nanocarriers (NLC-QU) [ 25 , 26 ]. The determination of the drug content was performed on an HPLC (Agilent 1100 series).…”
Section: Methodsmentioning
confidence: 99%
“…As a result, a system with better stability, controlled release of the photosensitive agent and modified behavior in the gastrointestinal tract can be obtained. To improve the oral bioavailability of quercetin numerous other systems were produced, such as SNEDDS enhancing brain targeting [190], SNEDDS using synergistic effect of mixing antioxidants [191], modification of polymer-lipid hybrid nanoparticles by cholate [166] or lipid-based nanocarriers consisting of castor oil, lecithin and PEG 600-stearate [169].…”
Section: Advances In Oral Deliverymentioning
confidence: 99%